Degenerating and Painful Human Intervertebral Discs Release Pronociceptive Factors and Increase Neurite Sprouting and CGRP via Nerve Growth Factor. (May 2014) - Krock, E.; Rosenzweig, D. H.; Chabot-Dore, A. J.; Jarzem, P.; Weber, M. H.; Ouellet, J. A.; Stone, L. S.; Haglund, L.
Introduction: Increasing evidence suggests that healthy and painless intervertebral discs (IVDs) are largely aneural and that degenerating and painful IVDs often are innervated. 1 Many inflammatory factors are unregulated in disc degeneration, such as interleukin (IL)-1β, IL-6, and tumor necrosis factor-α (TNF-α), and are believed to play important roles in degeneration and pain. 2, 3 Increased levels of neurotrophins, such as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF), have also been associated with disc degeneration and could potentiate disc innervation. 4 Inflammatory factors and neurotrophins can also have nociceptive roles that promote the development of chronic pain. While increased levels of inflammatory and nociceptive factors have been found by histological analysis in degenerating discs, in disc cell cultures, and in animal models, 3 the ability of degenerating intervertebral discs from chronic low back pain patients to release increased levels of nociceptive factors compared with healthy discs from pain free donors is unknown. An understanding of the ability of degenerating discs to release nociceptive factors that may sensitize neurons and the mechanisms involved will provide evidence to develop effective pain management strategies. Materials and Methods: Degenerating, painful IVDs were collected from patients undergoing surgery for low back pain and healthy, painless IVDs were collected from human organ donors through Transplant Quebec. IVDs were cultured ex vivo for 48 hours and the conditioned media was collected. Protein arrays were used to assess relative quantities of 23 cytokines and chemokines and enzyme-linked immunosorbent assay (ELISA) kits were used to quantify TNF-α, NGF, and BDNF in the conditioned media. PC12 cells, a neuronal-like cell line, were exposed to the conditioned or NGF supplemented media and neurite sprouting was analyzed. Mouse sensory neurons were isolated from dorsal root ganglia and treated with conditioned media. Neuronal expression of CGRP, a peptide involved in pain modulation, was compared with the total number of neurons that were stained with PGP 9.5, a general neuronal marker and the percentage of CGRP immunoreactive neurons was determined. To determine the role of NGF in neurite sprouting and CGRP regulation NGF supplemented or degenerating IVD conditioned media was incubated with an anti-NGF antibody. Cytokine array data were analyzed by unpaired t -tests and neurite sprouting and CGRP expression was assessed by one-way ANOVA. Results: Cytokine arrays found that degenerating painful IVDs released significantly higher levels of a majority of the factors represented in the array as compared with healthy painless IVDs. Many of them are nociceptive factors including IFN-γ, IL-6, MCP-1, GRO-α. IELISA assays demonstrated higher levels of the NGF and BDNF, in media from degenerating painful discs. Increased neurite growth was observed in PC12 cell cultures maintained in degenerating IVD media compared with healthy IVD media ( p < 0.001). Anti-NGF antibodies were able to prevent neurite growth to the level found in healthy IVD media cultures ( p = 0.929). In addition, a greater number of the mouse neurons cultured in degenerating IVD conditioned media were CGRP immunoreactive compared with those cultured in healthy IVD media ( p = 0.007). The number of CGRP immunoreactive neurons was significantly reduced in the presence of anti-NGF antibodies ( p > 0.999). Conclusion: Increased levels of pronociceptive and neurotrophic factors released by degenerating painful IVDs could potentiate IVD innervation and neuronal hypersensitization. Prolonged neuronal exposure to these factors could promote the development of chronic pain. The induced neurite growth and CGRP expression suggests that degenerating IVDs secrete factors that can lead to IVD innervation and nociception. NGF inhibition studies found NGF released by degenerating IVDs is required for the increased neurite growth and CGRP expression, providing evidence to support an important role for NGF in chronic low back pain associated with disc degeneration. The roles of factors besides NGF in disc degeneration require further investigation. These results suggest that degenerating, painful IVDs produce factors, which may cause neoinnervation and pain in vivo. Furthermore, this study provides evidence to support further development of anti-NGF therapies as a pain management strategy for low back pain associated with disc degeneration. Disclosure of Interest None declared References Freemont AJ, Peacock TE, Goupille P, Hoyland JA, O'Brien J, Jayson MI. Nerve ingrowth into diseased intervertebral disc in chronic back pain. Lancet 1997;350(9072):178–181 Le Maitre CL, Freemont AJ, Hoyland JA. The role of interleukin-1 in the pathogenesis of human intervertebral disc degeneration. Arthritis Res Ther 2005;7(4):R732-R745 Wuertz K, Haglund L. Inflammatory mediators in intervertebral disk degeneration and discogenic pain. Global Spine J 2013;3(3):175–184 Richardson SM, Purmessur D, Baird P, Probyn B, Freemont AJ, Hoyland JA. Degenerate human nucleus pulposus cells promote neurite outgrowth in neural cells. PLoS ONE 2012;7(10):e47735